2015
DOI: 10.1021/acs.joc.5b01160
|View full text |Cite
|
Sign up to set email alerts
|

Palladacycle-Catalyzed Carbonylative Suzuki–Miyaura Coupling with High Turnover Number and Turnover Frequency

Abstract: This work reports the carbonylative Suzuki-Miyaura coupling of aryl iodides catalyzed by palladacycles. More importantly, the palladacycles have been used to generate high turnover numbers (TON's) and turnover frequencies (TOF's). A range of aryl iodides can be coupled with arylboronic acids, generating TON's in the range of 10(6) to 10(7) and TOF's in the range of 10(5) to 10(6) h(-1). Comparison of the palladacycles with a conventional palladium source shows their superiority in generating high TON's and TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 50 publications
1
29
0
1
Order By: Relevance
“…[1][2][3][4] During the past few decades, great efforts have been devoted to develop highly efficient catalytic systems for this transformation. Various homogeneous [39][40][41] and immobilized molecular catalysts [42][43][44][45][46] have been developed. However, most of the immobilized molecular catalysts suffered from either the formation of less active palladium nanoparticles or the obvious palladium leaching.…”
Section: Carbonylative Suzuki Coupling Of Aryl Halidesmentioning
confidence: 99%
“…[1][2][3][4] During the past few decades, great efforts have been devoted to develop highly efficient catalytic systems for this transformation. Various homogeneous [39][40][41] and immobilized molecular catalysts [42][43][44][45][46] have been developed. However, most of the immobilized molecular catalysts suffered from either the formation of less active palladium nanoparticles or the obvious palladium leaching.…”
Section: Carbonylative Suzuki Coupling Of Aryl Halidesmentioning
confidence: 99%
“…[20,21] Since 1993, many publications have reported using various palladium catalysts in carbonylative Suzuki−Miyaura coupling, but this method has some drawbacks, such as high catalyst loading, high CO pressure, long time, high temperature, and low selectivity control, and in addition most of these reactions need high loading of phosphine ligands even with aryl iodides. [7,20,[22][23][24][25][26][27][28][29][30][31] For the past two decades, serious effort has been put into the development of N-heterocyclic carbene (NHC) metal complexes and a revolution has been achieved, especially in their applications as organometallic catalysts. [32][33][34][35][36][37][38] This has been attributed to the ability of NHC ligands to donate σ electrons, which leads to the formation of strong and stable bonds with the metals and prevents formation of inactive palladium black in the catalytic cyclic.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, these coupling reactions typically proceed in organic solvents, but they have also been applied successfully in green solvents such as water and ionic liquids . Carbonylative Suzuki cross‐coupling reactions are generally catalysed by palladium nanoparticles, in situ generated palladium complexes with phosphines or N‐heterocyclic carbene ligands or various commercially available palladium complexes, palladium on carbon, palladium nanoparticles immobilized on supported ionic liquid‐like phases, palladium supported on hollow magnetic mesoporous spheres, palladium nanoparticles supported on nickel pyrazolate or palladacycles . However, to the best of our knowledge, there has been no study of carbonylative cross‐coupling reactions of arylboronic acids with aryl iodides catalysed by PN‐type bidentate iminophosphine ligand‐based palladium complexes …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Carbonylative Suzuki cross-coupling reactions are generally catalysed by palladium nanoparticles, [10,11] in situ generated palladium complexes with phosphines or N-heterocyclic carbene ligands or various commercially available palladium complexes, [7,[12][13][14][15] palladium on carbon, [16] palladium nanoparticles immobilized on supported ionic liquid-like phases, [6] palladium supported on hollow magnetic mesoporous spheres, [17] palladium nanoparticles supported on nickel pyrazolate [18] or palladacycles. [19] However, to the best of our knowledge, there has been no study of carbonylative cross-coupling reactions of arylboronic acids with aryl iodides catalysed by PN-type bidentate iminophosphine ligand-based palladium complexes. [20] In the study reported in this paper, we prepared, characterized and investigated the electrochemical behaviour of PN-type iminophosphine ligands and their Pd(II) complexes.…”
Section: Introductionmentioning
confidence: 99%